Leveraging Family History in Case-Control Analyses of Rare Variation. Issue 2 (1st February 2020) - Solis-Lemus, Claudia R; Fischer, S Taylor; Todor, Andrei; Liu, Cuining; Leslie, Elizabeth J; Cutler, David J; Ghosh, Debashis; Epstein, Michael P
Abstract: Standard methods for case-control association studies of rare and common variation often treat disease outcome as a dichotomous phenotype. However, recent studies have demonstrated that cases with a family history of disease can be enriched... Standard methods for case-control association studies of rare variation often treat disease outcome as a dichotomous phenotype. However, both theoretical and experimental studies have demonstrated that subjects with a family history of disease can be enriched for risk variation relative to subjects without such history. Assuming family history information is available, this observation motivates the idea of replacing the standard dichotomous outcome variable used in case-control studies with a more informative ordinal outcome variable that distinguishes controls (0), sporadic cases (1), and cases with a family history (2), with the expectation that we should observe increasing number of risk variants with increasing category of the ordinal variable. To leverage this expectation, we propose a novel rare-variant association test that incorporates family history information based on our previous GAMuT framework for rare-variant association testing of multivariate phenotypes. We use simulated data to show that, when family history information is available, our new method outperforms standard rare-variant association methods, like burden and SKAT tests, that ignore family history. We further illustrate our method using a rare-variant study of cleft lip and palate.